Gossypol Promotes Degeneration of Ovarian Follicles in Rats - Ivana Cristina Nunes Gadelha; Michelly Fernandes de Macedo; Sílvia Catarina Salgado Oloris; Marilia Martins Melo; Benito Soto-Blanco (The Scientific World Journal)
The present study aimed to determine if gossypol interferes with ovarian follicles in rats. Twenty-four female Wistar rats were assigned to two equal groups: one control group and the other dosed with gossypol (25 mg/kg/day, subcutaneously) for 15 days. Ovarian follicles were histologically classified according to the stage of development and as normal or atretic. Gossypol treatment reduced the length of estrous with an increase in the duration of the diestrus phase. This compound was responsible for reduced serum levels of T4 and progesterone. Treatment with gossypol was responsible for a significant reduction in the number of normal ovarian follicles and a significant increase in the number of atretic follicles, both in all stages of development. Thus, treatment of rats with gossypol was responsible for reduction in the number of viable follicles and changes in hormone levels that resulted in interference of the estrous cycle.